Evaluation of Efficacy and Tolerability of Fixed Dose Combination of Rifaximin and Metronidazole in The Management of Acute Diarrhea - Faruqui, Arif Ahmad (The Indonesian Society for Digestive Endoscopy, 2023)
Background: Infectious diarrhea is endemic in many parts of the world. It is generally mixed in etiology involving virus, bacteria, and parasite. Antibiotics belonging to fluoroquinolones class are most commonly used but are beneficial only in certain types of acute diarrhoea with side-effects like tendinopathy, arthropathy, neuropathy, arrhythmia, hypoglycemia, and hyperglycemia. Rifaximin with its unique mechanism, along with established metronidazole is proposed as a treatment option for acute diarrhea caused due to mixed gastrointestinal infections. The aim of this study is to evaluate the efficacy and tolerability of a fixed dose combination of rifaximin and metronidazole in the empirical management of acute diarrhea.Method: An open-label, non-comparative, non-randomized, multicenter trial was conducted in 238 patients presenting with acute diarrheal episodes involving various etiologies. Patients were given fixed dose combination tablet containing rifaximin 200 mg and metronidazole 400 mg twice a day for 5 days. Primary outcomes were change from baseline in number of soft or watery stools, fever, nausea, vomiting, abdominal pain, and gas/flatulence at day 5.Results: In final analysis 150 patients were included, as 88 patients lost to follow up. After 5 days of therapy, mean number of watery stools per day were reduced from 7.133 ± 2.055 to 0.733 ± 0.833 (p 0.0001). Minor incidences of gastritis, nausea, and metallic taste were reported.Conclusion: Combination of rifaximin and metronidazole significantly reduces number of watery stools and associated symptoms and is a clinically effective and safe option in the empirical management of acute diarrhea of various etiologies.